Dine @ 3 Sdn Bhd / Mohd Zikry Hj. Zulkifle ... [et al.] - Hj. Zulkifle, Mohd Zikry; Zulkuply, Rushaida; Hayon, Ili Farhana; Hj . Mohd Husin, Mohd Shahril; Mohamed Hazri, Mohamed Zulfikar (Faculty of Hotel and Tourism Management, 2005)
Nowadays, in Malaysia there are many entrepreneurs involves in business especially in food production. Since, there are many women who are working and didn't have many times to cook for their family, so we Dine@3 Sdn.Bhd take this advantage to open a business dealing with food which can give a good profit.